EVALUASI IN VITRO PADA RANSUM YANG MENGANDUNG KULIT MELINJO (Gnetum gnemon L.) - Nina Suryanti; Eka Maya Rahmawati; Iman Hernaman; Ana Rohana Tarmidi (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2021)
Melinjo cod has the potential as an energy source of feed for ruminant. This study aims to evaluate rations containing melinjo cod in vitro. The study was conducted experimentally using a completely randomized design. Data collected were analyzed for variance analysis followed by Duncan's test. The treatment is a type of ration containing 0% (R1), 10% (R2), 20% (R3), 30% (R4), and 40% (R5) melinjo cod, each of which is repeated 4 times. Then the ration was evaluated in vitro. The results showed that the use of melinjo cod in the ration produced a significant difference (P <0.05) on fermentability and digestibility in vitro. The use of melinjo cod did not make a difference to the concentration of N-NH3, but resulted in an increase (P<0.05) in the concentration of volatile fatty acids and high digestibility of dry matter and organic matter up to 30% with averages of 155.90 mL, 66.79% and 67.81%. It can be concluded that melinjo cod can be used in ration as much as 30%.